Zymbilan®-PSO cream with nano-encapsulated RetileX-A®-PRO mitigates the clinical severity and relieves the symptoms of chronic plaque psoriasis: an interventional clinical study - Wadstein, Jan (International Journal of Research in Dermatology, 2021)
Background: Skin psoriasis is a serious inflammatory disorder with increased risk of rheumatic, cardiometabolic and psychosocial complications. At present, >50% of patients are dissatisfied with their treatment; thus, novel approaches are in high clinical demand. Retinoids are a major group of anti-psoriatic compounds; nonetheless, dose-dependent topical side effects have limited their effective topical application. RetileX-A®-PRO (Pharma Medico, Aarhus, Denmark) is a novel nano-encapsulated retinol ester designed to minimise the risk of skin irritation. The proprietary nano-encapsulation technology used in this compound can protect retinoid molecules from degradation, and thereby prolong and stabilise its release profile. The safety and efficacy of RetileX-A®-PRO were evaluated in this study. Methods: 45 patients (58% female, aged 18-80 years) with mild to moderate skin psoriasis were enrolled in a 4-week interventional study. Participants were treated once daily with Zymbilan®-PSO cream with RetileX-A®-PRO and evaluated both objectively and subjectively at baseline, after 8 hours and at endpoint. Results: Our observations demonstrated that Zymbilan®-PSO cream possesses both short-term and long-term anti-psoriatic effects. Shortly after application, objective skin characteristics were improved, and itching reduced in >84% of subjects. At endpoint, 87% of skin lesions improved, 9% did not change and 4% progressed as assessed by a dermatologist. Patients’ self-evaluation yielded similar results: 78% judged Zymbilan®-PSO cream as a ‘good’ to ‘very good’ skin care product with suitable cosmetic parameters. No side effects recorded in 95% of participants. Conclusions: In conclusion, Zymbilan®-PSO cream is a well-tolerated treatment that can mitigate both clinical severity and subjective symptoms of chronic skin psoriasis.